2013
DOI: 10.3109/17435390.2013.837208
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose gold nanoparticles exert subtle endocrine-modulating effects on the ovarian steroidogenic pathwayex vivoindependent of oxidative stress

Abstract: Gold nanoparticles (GNPs) have gained considerable attention for application in science and industry. However, the untoward effects of such particles on female fertility remain unclear. The objectives of the present study were to (1) examine the effects of 10-nm GNPs on progesterone and estradiol-17β accumulation by rat ovaries ex vivo and (2) to identify the locus/loci whereby GNPs modulate steroidogenesis via multiple-reference gene quantitative real-time RT-PCR. Regression analyses indicated a positive rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, the complexity of signalling means modulating autophagy with NPs could bring safety concerns. Earlier studies of NPs’ impact on cell systems suggest that dosage is a critical parameter in pathway modulation [ 37 , 38 ]. This type of study could deliver additional insights in enabling better safe-by-design strategies for NPs used in consumer products and/or in drug delivery therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complexity of signalling means modulating autophagy with NPs could bring safety concerns. Earlier studies of NPs’ impact on cell systems suggest that dosage is a critical parameter in pathway modulation [ 37 , 38 ]. This type of study could deliver additional insights in enabling better safe-by-design strategies for NPs used in consumer products and/or in drug delivery therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The potential harmful effects of nanoparticles such as induction of cellular states of oxidative stress, modulation of enzyme activity, inflammation, and cell death include disruption of gonadal steroidogenesis-related biochemical and physiologic processes [ 16 ]. Larson et al [ 76 ] reported that gold nanoparticles could be a new class of ovarian endocrine-inhibiting compounds if exposed for extended periods or at high concentrations as they disrupt the production of sex-steroid hormones, resulting in reproductive problems in humans and animals [ 76 ]. By contrast, Gallus domesticus treated with silver nanoparticles showed no significant differences in progesterone levels between the granulosa and theca layers, but a progressive reduction in estradiol and testosterone levels was observed in theca cells.…”
Section: Impact On the Female Reproductive Systemmentioning
confidence: 99%
“…17 As revealed by an ex vivo study on rat ovaries, nanoparticles can still exert noxious effects by disrupting the secretion and bioavailability of endocrine molecules even if they do not physically interact with the oocyte as just tens of particles of 10 nm Au particles were capable of significantly altering the biosynthesis of steroid hormones. 18 The available literature suggests that nanoparticles have the potential to jeopardise the normal function of the male and female reproductive system. Despite these alarming signs, there are no clinical studies to explore the potential risk in fertility and fecundity posed by human exposure to engineered nanoparticles.…”
Section: Introductionmentioning
confidence: 99%